Fatigue increases ankle sprain risk in badminton players: A biomechanical study - Herbaut, A.; Delannoy, J. (Journal of Sports Sciences, 2020)
Ankle sprains are the most common injury in regular badminton players and usually occur at the end of a match or training. The purpose of the present study was to examine the influence of fatigue produced by badminton practice on the lower limb biomechanics of badminton players. It was hypothesized that fatigue induces ankle kinematic and lower leg muscle activity changes which may increase the risk of ankle sprain. Ankle kinematics, ankle kinetics and muscles activities of 17 regular badminton players were recorded during lateral jumps before and after an intense badminton practice session. Post-fatigue, ankle inversion at foot strike and peak ankle inversion increased (+2.6°, p = 0.003 and +2.5°, p = 0.005, respectively). EMG pre-activation within 100 ms before foot landing significantly decreased after fatigue for soleus (-23.4%, p = 0.031), gastrocnemius lateralis (-12.2%, p = 0.035), gastrocnemius medialis (-23.3%, p = 0.047) and peroneus brevis (-17.4%, p = 0.036). These results demonstrate impaired biomechanics of badminton players when fatigue increases, which may cause a greater risk of experiencing an ankle sprain injury.